The edge of nowhere - George, Elizabeth, 1949- (New York : Viking, 2012)
When her mother abandons her on Whidbey Island, Washington, a fourteen-year-old girl with psychic abilities meets a Ugandan orphan with a secret.
Keywords: Abandoned children -- Fiction; Psychic ability -- Fiction; Secrets -- Fiction; Whidbey Island (Wash.) -- Fiction